Correction: Alencar et al. Assessment of the Bearing Capacity of Bridge Foundation on Rock Masses. Appl. Sci. 2021, 11, 12068 - Ana Alencar; Rubén Galindo; Claudio Olalla Marañón; Svetlana Melentijevic (Applied Sciences, 2023)
Svetlana Melentijevic was not included as an author in the original publication [...]